A programmed parametric synthesizer - PATRYN, Ryszard (Archives of Acoustics, 1981)
The synthesizer described generates signals with a duration of the pitch period, which follow the waveform of the respective segments of a natural speech signal. Parameters of each segment are determined on the basis of digital data using a computer. Some of these data are used to generate the constituents of a signal in digital to analogue convertors and some to shape the waveform obtained. The paper also gives the range of the available parameters of the sounds generated and also some examples of programmes.